Kuiyku mabaigal Waii & Sobai - Laza, Aidan, 1922-; Tipoti, Alick, 1975- (Broome, Western Australia: Magabala Books, 1998)
This story tells of the Torres Strait Islands before the coming of missionaries.
White
Text in English and Kala Lagaw Ya language, translated from Kala Lagaw Ya.
Keywords: Folklore -- Queensland -- Badu Island; Kalaw Lagaw Ya / Kala Lagaw Ya language (Y1) (Qld TSI SC54-07); Kalaw Lagaw Ya / Kala Lagaw Ya language (Qld TSI SC54-07); Torres Strait Islanders (Qld TSI SC54, SC55); Stories and motifs - Cultural heroes; Badu / Mulgrave Island (Qld TSI SC54-11); Australian